Dynamics of macroparticle in a weakly collisional plasma - Romashchenko, E.V.; Bizyukov, A.A.; Girka, I.О. (Вопросы атомной науки и техники, 2019)
The transport of a macroparticle (MP) in an expanding cathodic vacuum arc plasma, which interacts with a background gas, is investigated. The influence of ion-neutral collisions on MP is studied in the framework of self-consistent model based on the fluid approach and orbital motion limited theory. It is found that the electrostatic re-flection of MP increases with collisionality as a consequence of the increased negative potential of MP. A compari-son of the ion drag and neutral drag forces governing the MP dynamics is made. It is shown that the ion drag force decreases with the ion collisionality, while the neutral drag force increases. Досліджено транспорт макрочастинки (МЧ) у плазмі, що розширюється, катодної вакуумної дуги при взаємодії з газом. Вплив зіткнень іонів з нейтралами на МЧ вивчається на підставі самоузгодженої моделі, що базується на теорії рідини та теорії обмеженого орбітального руху. Отримано, що електростатичне відбиття МЧ зростає із зіткненністю внаслідок збільшення від’ємного потенціалу МЧ. Зроблено порівняння сили іонного захвату та сили тертя з боку нейтралів, які визначають динаміку МЧ. Було показано, що сила іонного захвату зменшується із зіткненністю в той час, як сила тертя з боку нейтралів збільшується. Исследован транспорт макрочастицы (МЧ) в расширяющейся плазме катодной вакуумной дуги при взаимодействии с газом. Влияние столкновений ионов с нейтралами на МЧ изучается в рамках самосогласованной модели, основанной на гидродинамическом подходе и теории ограниченного орбитального движения. Получено, что электростатическое отражение МЧ увеличивается со столкновительностью вследствие увеличения отрицательного потенциала МЧ. Проведено сравнение силы ионного увлечения и силы трения со стороны нейтралов, которые определяют динамику МЧ. Показано, что сила ионного увлечения уменьшается со столкновительностью, в то время как сила трения со стороны нейтралов увеличивается.